Humor–robot interaction: a scoping review of the literature and future directions - Oliveira, R.; Arriaga, P.; Axelsson, M.; Paiva, A. (International Journal of Social Robotics, 2021)
Humor is a pervasive feature of everyday social interactions that might be leveraged to improve human-robot interactions (HRI). Our goal is to evaluate how the use of humor can improve HRI and enhance the user’s perception of the robot, as well as to derive implications for future research and development of humorous robots. We conducted a systematic search of 7 digital libraries relevant in the areas of HRI and Psychology for papers that were relevant to our goal. We identified 431 records, published between 2000 and August of 2020, of which 12 matched our eligibility criteria. The included studies reported the results of original empirical research that involved direct or video-mediated interaction of humans and robots. Humor seems to have a positive effect in improving the user’s perception of the robot, as well as the user’s evaluation of the interaction. However, the included studies present a number of limitations in their approaches to robotic humor that need to be surpassed before reaching a final verdict on the value of humor in HRI.